2018
DOI: 10.1209/0295-5075/123/47004
|View full text |Cite
|
Sign up to set email alerts
|

Nodeless superconductivity in the SnAs-based van der Waals-type superconductor NaSn 2 As 2

Abstract: We grew the single crystals of the SnAs-based van der Waals (vdW)-type superconductor NaSn2As2 and systematically measured its resistivity, specific heat, and ultralow-temperature thermal conductivity. The superconducting transition temperature Tc = 1.60 K of our single crystal is 0.3 K higher than that previously reported. A weak but intrinsic anomaly situated at 193 K is observed in both resistivity and specific heat, which likely arises from a charge-densitywave (CDW) instability. Ultralow-temperature therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
4
28
0
Order By: Relevance
“…[17][18][19][20][21] The residual resistivity ratio (300 K)/(0.5 K) is estimated to be 1.3, which is comparable to those of related materials. [13][14][15]17,18,20,21,35 Due to the layered structure of Li1-xSn2+xP2, we investigated its anisotropy in resistivity with respect to uniaxial hot pressing direction above room temperature. As shown in Figure 4(a), the anisotropy in the present samples is not significant.…”
Section: Transport Propertiessupporting
confidence: 51%
“…[17][18][19][20][21] The residual resistivity ratio (300 K)/(0.5 K) is estimated to be 1.3, which is comparable to those of related materials. [13][14][15]17,18,20,21,35 Due to the layered structure of Li1-xSn2+xP2, we investigated its anisotropy in resistivity with respect to uniaxial hot pressing direction above room temperature. As shown in Figure 4(a), the anisotropy in the present samples is not significant.…”
Section: Transport Propertiessupporting
confidence: 51%
“…No superconducting transition is observed down to 0.5 K, unlike for Na1-xSn2P2 and NaSn2As2. [17][18][19][20][21] The residual resistivity ratio (300 K)/(0.5 K) is estimated to be 1.3, which is comparable to those of related materials. [13][14][15]17,18,20,21,35 Due to the layered structure of Li1-xSn2+xP2, we investigated its anisotropy in resistivity with respect to uniaxial hot pressing direction above room temperature.…”
Section: Transport Propertiessupporting
confidence: 51%
“…16 It has also been demonstrated that NaSn2As2 and Na1-xSn2P2 show superconducting transitions, meaning that these compounds can also be categorized as novel layered superconductors. [17][18][19][20][21] As well as these ternary-phase materials, the binary tin phosphide Sn4P3 has been investigated as a rechargeable battery anode material. [22][23][24][25][26][27][28][29][30][31] For example, the high reversible capacity of 850 mA•h•g −1 has been achieved for a Na-ion battery with a Sn4P3/C composite anode.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] In addition to being thermoelectric materials, these compounds are interesting because they undergo superconducting transitions at low temperatures. [44][45][46][47][48] compounds EuIn2As2−xPx (x = 0 to 2) and SrSn2As2. In the early stage of this work, we first investigated the thermoelectric properties of SrSn2As2.…”
Section: Introductionmentioning
confidence: 99%